The STEM-based Mathematics Module Development to Improve Numerical Literacy and Learning Self-Directness of Fifth Graders - Purniawan Purniawan; Isti Hidayah; YL Sukestiyarno (Journal of Primary Education, 2022)
Modules are one of the teaching materials used to assist the learning process. This research developed a STEM-based mathematics module. This Research & Development (r&d) adopted the ADDIE method, consisting of five stages, starting from Analysis, Design, Development, Implementation dan Evaluation. The analysis phase begins by examining the demands for instructional materials. Followed by the Design stage, which entails defining objectives and materials, the Development stage, which entails making the design a reality, the Implementation stage, which entails determining the product's effectiveness, and the Evaluation stag. Collected the data with an interview, test, questionnaire, and observation. The number of respondents consisted of 37 learners in the academic year 2022/2023.The result showed that 1) the characteristics of the developed module had the focus to improve the numerical literacy and self-directedness of learners; 2) the module reliability was excellent with a very valid category; 3) The readability of the module was higher than 60% or categorized readable; 4) the module was practice proven with a percentage of 84% ; 5) and the module was effective and could influence the improvement of numerical literacy and learning self-directedness. Concluded that the STEM-based mathematics module development was effective to improve numerical literacy and learning self-directedness.